Indolent course of brainstem tumors with K27M‐H3.3 mutation. Issue 3 (2nd December 2019) - Baroni, Lorena V.; Solano‐Paez, Palma; Nobre, Liana; Michaeli, Orli; Hawkins, Cynthia; Laughlin, Suzanne; Bartels, Ute; Ramaswamy, Vijay; Bouffet, Eric
Abstract: Diffuse intrinsic pontine glioma (DIPG) is characterized by a short history of brainstem symptoms and well‐known magnetic resonance imaging features with a fatal outcome. However, we report three unusual cases of brainstem tumors with an initial indolent and protracted course, which subsequently developed the classical imaging and clinical features of DIPG. Our findings support this notion that K27M is an early event in development and suggest that the emergence of additional events resulted in rapid progression after a long period of latency. Identification of such markers of aggressive behavior in the context of an indolent course is needed for better characterization and treatment management.